Bucket Brigades to Increase Productivity in a Luxury Assembly Line. (13th August 2013) - De Carlo, Filippo; Borgia, Orlando; Tucci, Mario
One of the most challenging issues in manual assembly lines is to achieve the best balance of workloads. There are many analytic approaches to solve this problem, but they are often neglected, since they are time-consuming and require high level engineering skills. Fashion bags packaging lines must comply with a number of different products with low production volumes, while the organization of the line is often under the mere responsibility of the foreman, who balances workloads in an empirical way. The aim of this work is to evaluate the effectiveness of the arrangement of bucket brigades (BBs) for an assembly line of luxury handbags. To do this, it was decided to perform a testing activity in a company producing fashion handbags in order to compare the self-made design with the BBs and with a simple assembly line balancing problem algorithm. The originality of this research lies in the fact that there are no studies in the literature on BBs applied to the packaging of highly variable small batches. The results were excellent, showing the advantages of BBs in terms of flexibility, the reduction of work in the process and the ability to handle small anomalies.